Influence of dispersing additive on asphaltenes aggregation in model system; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Gorshkov A. M. Anton Mikhailovich; Shishmina L. V. Lyudmila Vsevolodovna; Tukhvatullina A. Z.; Ismailov Yu. R.; Ges G. A. (Latest Research in Hydrocarbon Refining, 2016)
Title screen